The amygdala central nucleus and appetitive Pavlovian conditioning: lesions impair one class of conditioned behavior - Gallagher, M (J Neurosci, 1990)
Rats with neurotoxic lesions of the amygdala central nucleus (CN) were trained using appetitive Pavlovian conditioning procedures. Conditioned responses (CRs) that are representative of 2 classes of behavior were monitored. One type of CR resembled the orienting responses that were elicited by the conditioned stimuli (CSs) prior to pairing with food reinforcement: the other type of CR resembled the behavior elicited by food reinforcement itself. Holland (1977, 1984) has referred to these as CS-generated and unconditioned stimulus (US)-generated CRs, respectively. During differential conditioning, some lesioned and unlesioned rats received reinforced presentations of a visual cue and nonreinforced presentations of an auditory cue, and the others in each lesion condition received reinforced auditory and nonreinforced visual cue presentations. Relative to the control group, the CN-lesioned rats were impaired in the acquisition of CS-generated CRs to both visual and auditory CSs. Orienting responses and habituation to the CSs were, however, comparable for the lesion and control groups. Moreover, rats with CN lesions readily acquired the US-generated CRs. Thus, a specific class of conditioned behavior was impaired by CN damage. Many studies using aversive Pavlovian procedures have suggested that CN lesions impair fear conditioning. The present results suggest another role for CN in the conditioning of orienting/attentional responses.